System expansion is needed to handle the multifunctionality of food items in environmental impact assessment - Leinonen, Ilkka; Korkalo, Pasi; Hietala, Sanna; Usva, Kirsi; Saarinen, Merja (Springer Nature, 2025)
Any comparison of the environmental impacts of different food items should be based on their functionality, such as providing nutrients and energy. In this study, a Life Cycle Assessment (LCA) approach was developed for quantifying the Global Warming Potential of different protein sources. This approach is based system expansion, which, according to the LCA standards, is a preferred method for handling multifunctionality, but still largely ignored in nutritional LCA so far. The method makes it possible to compare different individual food items based on their function in human nutrition. In this case study, the provision of balanced amino acids was selected as such a function, and provision of energy for metabolic process was handled as a “by-product”. This new approach reinforces the current methodology of nutritional LCA and improves its ability to compare the environmental performance of different food items with partially different functionality.
Keywords: food items; food; environmental impact assessment; Life Cycle Assessment; LCA; multifunctionality